1994
DOI: 10.1111/j.1748-1716.1994.tb09810.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ageing on ultrastructure of slow and fast skeletal muscle tendon in rabbit Achilles tendons

Abstract: This reports presents the changing morphological characteristics of collagen and fibroblasts in the soleus and gastrocnemius muscle tendon of female Japanese white rabbits with ageing. The fibroblasts decreased in number per 37 microns 2 with ageing in each group, and their morphology became longer and more slender through ageing. The mean fibril area and diameter of the collagen fibrils of soleus muscle tendon (SMT) and lateral gastrocnemius muscle tendon (GMT) in 8- to 10-month old rabbits were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 19 publications
1
49
1
1
Order By: Relevance
“…It has been previously shown that heavy slow resistance training is associated with changes in fibril morphology (Kongsgaard et al 2010), and in addition, aging has been observed to reduce the size and/or density of collagen fibrils both in animals (Curwin et al 1994;Nakagawa et al 1994;Parry et al 1978;PattersonKane et al 1997) and humans (Sargon et al 2005;Strocchi et al 1991). In the present study, we did not find any significant effects on fibril morphology with age or training, although there was a tendency for lower collagen fibril density with age (p=0.084).…”
Section: Collagen Fibril Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that heavy slow resistance training is associated with changes in fibril morphology (Kongsgaard et al 2010), and in addition, aging has been observed to reduce the size and/or density of collagen fibrils both in animals (Curwin et al 1994;Nakagawa et al 1994;Parry et al 1978;PattersonKane et al 1997) and humans (Sargon et al 2005;Strocchi et al 1991). In the present study, we did not find any significant effects on fibril morphology with age or training, although there was a tendency for lower collagen fibril density with age (p=0.084).…”
Section: Collagen Fibril Morphologymentioning
confidence: 99%
“…It appears that endurance training in aging animals yield a stronger and more compliant tendon (Gosselin et al 1998;Viidik et al 1996;Simonsen et al 1995;LaCroix et al 2013;Nielsen et al 1998), but this remains to be confirmed in a human model. Furthermore, at the microstructural level, the size and/or density of tendon collagen fibrils seems to be reduced with aging (Curwin et al 1994;Nakagawa et al 1994;Partington and Wood 1963;Patterson-Kane et al 1997), but if these age-related adaptations are influenced by physical activity remains unknown (Edwards et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This result seems to indicate that this test can be very useful for measuring effects of joints supplementation or another method for the treatment of joints problems such as physiotherapy or exercise. Our results indicate an increase in linear stiffness of AT in the elderly with the administration of Ovomet ® , when the normal behavior is the decrease of this parameter with ageing [16][17][18], the opposite of what happens during the passage from childhood to adulthood (5 to 12 years) [19,20], which report an increase in linear stiffness of the AT as a consequence of weight gain and increased loads in tendon.…”
Section: Resultsmentioning
confidence: 76%
“…Morphological changes are evident in both collagen and fibroblasts with increased animal age, fibroblasts decrease in number, while collagen fibril size increases (Nakagawa et al 1994). The number of crosslinks within collagen increases, such that the extracellular matrix becomes a stable multi-valent network (Robins et al 1973) leading to high viscoelasticity and low compliance (Rodrigues et al 1996).…”
Section: Connective Tissuementioning
confidence: 97%